Violence and Female Labor Supply - Zahra Siddique (Institute of Labor Economics (IZA), 2018)
This paper explores whether fear and safety concerns have an impact on behavior such as female labor supply in a developing country context. The effect of media reported physical and sexual assaults on urban women's labor force participation in India is investigated by combining nationally representative cross-sectional microeconomic surveys carried out between 2009 and 2012 with a novel geographically referenced data source on media reports of assaults. I find that a σ increase in lagged sexual assault reports within one's own district reduces the probability that a woman is employed outside her home by 0.44 percentage points (or 3.6% of the sample average). I find this effect despite ruling out several sources of unobserved heterogeneity. This effect is also robust to a number of sensitivity checks. Consistent with a model in which women make investments to overcome fear in the presence of economic incentives, I find that the effect of local violence on labor supply is weaker among women from poorer households. I also find this effect to be weaker among high caste Hindu women, but strong among Muslim women.
Keywords: J16; J22; 330; economics of gender; labor supply